Sheikh Cunayd Tomb in Kusar-Hazra Village (Azerbaijan): Restoration Errors And Reflections On The Importance of Preserving This Cultural Heritage - Çağlıtütüncigil, Ersel (Journal of Alevism-Bektashism Studies, 2024)
The art produced by the Turks for centuries has a unique identity and characteristic originality. Starting from Central Asia, the architectural works left behind primarily in Anatolia, Azerbaijan, Turkmenistan, Kazakhstan, Kyrgyzstan, Syria, Iraq, North Africa, and some other regions are the most vivid witnesses of this culture. The only way to truly understand our architectural heritage, which spans a vast geography, is to trace its developmental history, recognize and introduce the precursor examples outside Anatolia. In this regard, Azerbaijan, like other regions inhabited by the Turks, holds significant importance. Many answers and clues regarding the identity and origins of Turkish architecture can be found in the process that began with the establishment of the Seljuk and Safavid states in these lands, and in the cultural, civilizational, and architectural examples they produced during this period. This era, which made a significant contribution to the characteristic development of Turkish art, has also attracted great interest in the academic world. Azerbaijan’s architectural works, particularly those dating from the 11th to 16th centuries, although fewer in number compared to Anatolia, form a valuable bridge and transitional phase for the next stage of development. Therefore, it is of vital importance to correctly interpret, understand, protect, and preserve these works. The destruction of these works today does not only mean the disappearance of a few architectural monuments in Azerbaijan. It should also be understood as the severing of an important link in the great chain of our civilization.This article is based on the impressions and observations obtained through extensive research and studies conducted on the Sheikh Junayd Tomb. It emphasizes the place and significance of this architectural heritage from the 16th century, which dates to the Safavid period in Azerbaijan, within Turkish architectural art. Additionally, it discusses how this invaluable cultural heritage, with its historical and cultural significance, should be preserved more accurately and properly for future generations and why this is of critical importance.
Keywords: Azerbaijan; Sheikh Junayd; Turkish Architecture; Tomb; Cultural Heritage; Restoration